Cooperative tracking of vessel trajectories based on curved dynamic coordinates. Issue 5 (21st December 2018) - Chen, Yuqing; Yu, Shuanghe; Shen, Zhipeng; Guo, Ge
Abstract: A novel cooperative motion problem for multiple surface vessels is investigated based on multiple referential points and a terminal sliding mode control method. To overcome the difficulties of modeling some special tracking trajectories like rivers and coastlines in a traditional Cartesian coordinate system, a novel local curved‐dynamic coordinate system is constructed, and multiple referential points with given intervals on the curved coordinates are used as the consensus reference for the group. Then cooperative cruise of surface vessels is analyzed, based on which a local‐to‐global terminal sliding mode controller is designed to keep the relative pose of the dynamic unmanned vessels. At last, the formation trajectory constraint conditions are further discussed and some simulation results show the validity of the presented methods.